THE CALCULATION OF THE DISTRIBUTION OF POLLUTANTS IN BUILT-UP AREAS - Biliaiev, M. M.; Gunko, Ye. Yu. (Science and Transport Progress, 2007)
The 3D numerical model to simulate the toxic gas dispersion on industrial sites after accident ejections was developed. The model is based on the K-gradient transport model and equation of potential flow. The results of numerical experiment of atmosphere pollution and toxic hazard are presented.